Using Gamified Digital Media to Assist Working Parents in Maintaining Involvement in their Young Children’s Learning and Development - Ali, Wildan (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
This research explores the potential of gamified digital media platforms, in helping working parents stay actively involved in their young children's learning development. As work demands increase, parents often struggle to balance professional responsibilities with parenting duties. Using qualitative methods, including interviews and observations, a prototype app designed to engage both parents and children in educational activities was developed and tested. The findings suggest that digital platforms can significantly enhance parental involvement, offering flexible, accessible, and engaging ways for parents to support their children's learning in a meaningful and enjoyable way,